3D printed carbon aerogel microlattices for customizable supercapacitors with high areal capacitance. Issue 1 (15th December 2020) - Yuan, Shijia; Fan, Wei; Wang, Dong; Zhang, Longsheng; Miao, Yue-E.; Lai, Feili; Liu, Tianxi
Abstract : Carbon aerogel (CA) microlattices exhibits a controllable macrostructure by 3D printing as well as an interconnected porous microstructure from GP gel and presents a desirable areal and volumetric capacitance with high mass loading. Abstract : Desirable areal and volumetric capacitances of electrodes with high mass loading are of great significance for compact energy storage in practical applications. The key challenge remains in the structural design of electrodes with interconnected micro-/macro-networks for unimpeded electron and ion transport. Herein, three-dimensional (3D) printed carbon aerogel (CA) microlattices are designed with tunable thickness to realize high areal capacitance. By using polyamic acid (PAA) as a crosslinker, graphene oxide/polyamic acid (GP) ink exhibits ideal printability and formability to ensure the continuous printing of self-supported and programmable 3D structures. After subsequent freeze-drying and thermal treatment, the as-obtained CA exhibits not only a well-maintained macrostructure of the extruded shape but also a porous microstructure from the interconnected GP gel. As a result, the 3D printed CA microlattice presents a quasi-proportional increase in areal capacitance with thickness, achieving a desirable areal/volumetric capacitance (870.3 mF cm −2 /1.7 F cm −3 ) under high mass loading (15.3 mg cm −2 ) and large thickness (4.9 mm). This work offers a promising strategy to construct a customizable structure of a supercapacitor and provides new insights to dramatically improve the energy storage properties of microdevices with limited area.